The Clinton era and the U.S. business cycle : what did change? - Ullrich Heilemann; Heinz Josef Münch (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
The 1990s were the most prosperous decade in U.S. economic history. The paper analyses to which extent this period fits into preceding cyclical experience. This is done by classifying the period 1991-12 to 2000-12 with the help of a 4-phase classification scheme based on multivariate discriminance analysis. It is shown that in relation to the post 1970 experience, the ?fabulous decade? saw considerable shifts of influence between the 19 classifying variables. Most noteworthy are the much reduced influence of M2, Net Exports, and Unemployment on the one side and the increase of Real GNP, inflation, Government Expenditure and of Unit Labor Cost on the other side. This confirms interpretations of the fabulous decade as the result of a forbearing monetary policy made possible by a deficit targeting fiscal policy, low inflation and a productivity jump. However, the era looses some of its uniqueness when it is seen in the entire post WW II cycle history.
Keywords: O51; E29; E32; 519; U.S. business cycle; 4-phase scheme; discriminance analysis; Clinton era; Konjunktur; Wirtschaftswachstum; Konjunkturpolitik; Diskriminanzanalyse; Schätzung; Vereinigte Staaten